2021
DOI: 10.3389/fmolb.2021.645084
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Glycolysis-Related lncRNA Signature in Tumor Immune Microenvironment of Hepatocellular Carcinoma

Abstract: Purpose: The purpose of this study was to construct a novel risk scoring model with prognostic value that could elucidate tumor immune microenvironment of hepatocellular carcinoma (HCC).Samples and methods: Data were obtained through The Cancer Genome Atlas (TCGA) database. Univariate Cox analysis, least absolute shrinkage and selection operator (LASSO) analysis, and multivariate Cox analysis were carried out to screen for glycolysis-related long noncoding RNAs (lncRNAs) that could provide prognostic value. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…Additionally, it was reported that HCC forms a unique immune microenvironment in the process of development 40 . The study elucidated the crucial role of immune cell infiltration and immunotherapy, which might contribute to clinical strategies and clinical outcome prediction of HCC 41 . It has been reported that the inflammatory cells such as T lymphocytes activate HSCs, which are the major source of myofibroblasts in the liver 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was reported that HCC forms a unique immune microenvironment in the process of development 40 . The study elucidated the crucial role of immune cell infiltration and immunotherapy, which might contribute to clinical strategies and clinical outcome prediction of HCC 41 . It has been reported that the inflammatory cells such as T lymphocytes activate HSCs, which are the major source of myofibroblasts in the liver 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we compared the resulting GIlncSig to the latest published signatures related to lncRNAs; the first signature is the 4-lncRNA signature (BailncSig), and the second signature is the 3-lncRNA signature (LilncSig). The results showed that the AUCs for BailncSig (Bai et al, 2021), LilncSig (Li et al, 2021), and GILncSig OS were 0.724, 0.671, and 0.727 (Figure 7C). Based on the above results, GlncSig has independent research value in HCC.…”
Section: Independent Prognostic Analysis Of Gilncsigmentioning
confidence: 99%
“…For example, Wei et al developed a 20-miRNA signature to predict post-surgery survival in HCC patients [ 16 ]; Nault et al constructed a 5-gene signature to evaluate the overall survival in HCC patients [ 17 ]; Kim et al established a 233-gene signature to predict late recurrence in HCC patients [ 18 ]. Recently, prognostic signatures based on specific groups of genes such as glycolyis-related genes, metabolic-related genes and autophagy-related genes were also reported [ 19 21 ]. However, those multi-gene signatures of HCC mainly focus on overall survival and later recurrence, and few multi-gene signatures have been established to predict early recurrence in HCCs.…”
Section: Introductionmentioning
confidence: 99%